Design and evaluate the performance of a mechanical system for the release of Harmonia axyridis adults - Dong, Xiao-Ya; Tong, Xiang; Ma, Jing; Qiu, Bai-Jing (Frontiers in Plant Science, 2024)
Harmonia axyridis (H.axyridis) is the natural enemy of many aphid species. Traditional manual release of H.axyridis adults requires substantial manpower and release efficiency is low. Automatic mechanical devices can improve the efficiency of delivery. Based on H.axyridis adults' morphological size, a prototype release system for H.axyridis was designed, which considered the adhesion characteristics of H.axyridis adults. According to the measured physical characteristics of H.axyridis adults, the structural parameters of the mechanical system for the release of the H.axyridis adults were determined. The relationship of the quantity of release, the impeller rotating speed, and the time for the release of H.axyridis adults were constructed. The mechanism can quantitatively adjust the number of H.axyridis adults to meet a certain H.axyridis-aphids ratio. Combining the image processing technology with the camera function of a mobile phone, the maximum cross-sectional area method was used to count the H.axyridis adults in the designated area. Results showed that the impeller rotating speed had a significant effect on the survival rate of the H.axyridis adults. When the airflow velocities were 29.5m/s and 38.3 m/s, the survival rates of the H.axyridis adults were 93.8% and 94.5% at 4.2 rpm. The adhesion rate of the H.axyridis adults was 2.5-4.6%. This work will provide technical support for the research of biological control.